2010
DOI: 10.1007/s11356-010-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Body burdens of polybrominated diphenyl ethers in childbearing-aged women at an intensive electronic-waste recycling site in China

Abstract: Background, aim and scope This study is the first to investigate PBDE body burden with regard to the concurrent analyses of multiple human matrices, namely milk, placenta, and hair, collected from a group of childbearingaged women at an electronic waste (e-waste) recycling site to determine the partitioning of PBDEs in these different human matrices and the possible health risks imposed to infants at the e-waste recycling site. Methods and methods Five sets of milk, placenta, and hair samples were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 53 publications
6
46
0
1
Order By: Relevance
“…For breast milk, P 23 PCBs 52,99,101,128,138,153,170,180,183,187,77,81,105,114,118,123,126,156,157,167,169,189) were 206.05 ng g À1 lw for Pingqiao and 359.03 ng g À1 lw for Luqiao (Zhao et al, 2007). The arithmetic mean level of P 36 PBDEs 8,10,11,12,13,15,17,25,28,30,32,33,35,37,47,49,66,71,75,77,85,99,100,116,118,119,126,138,153,154,155,166,181,183,190) was found to be 117 ng g À1 lw in Taizhou (Leung et al, 2010). Dechlorane Plus levels found in the current study were relatively low compared with PCBs/PBDEs data from human exposure in Taizhou region mentioned above.…”
Section: Level Of Dechlorane Plus and Its Dechlorinated Analogmentioning
confidence: 95%
See 1 more Smart Citation
“…For breast milk, P 23 PCBs 52,99,101,128,138,153,170,180,183,187,77,81,105,114,118,123,126,156,157,167,169,189) were 206.05 ng g À1 lw for Pingqiao and 359.03 ng g À1 lw for Luqiao (Zhao et al, 2007). The arithmetic mean level of P 36 PBDEs 8,10,11,12,13,15,17,25,28,30,32,33,35,37,47,49,66,71,75,77,85,99,100,116,118,119,126,138,153,154,155,166,181,183,190) was found to be 117 ng g À1 lw in Taizhou (Leung et al, 2010). Dechlorane Plus levels found in the current study were relatively low compared with PCBs/PBDEs data from human exposure in Taizhou region mentioned above.…”
Section: Level Of Dechlorane Plus and Its Dechlorinated Analogmentioning
confidence: 95%
“…The monodechlorinated compound was also found in Ren et al (2009), but it was unquantified. Generally, PCBs and PBDE concentrations in human tissues from the contamination area in Taizhou range from dozens to hundreds ng g À1 lw (Zhao et al, 2007(Zhao et al, , 2010Leung et al, 2010). In a study in 2006 on P 5 PCBs 118,153,183,and 180) in blood from two typical e-waste recycling sites in Taizhou (Luqiao and Wenling), the arithmetic mean level was 204.2 ng g À1 lw for Luqiao and 83.8 ng g À1 lw for Wenling, and P 8 PBDEs 47,99,100,153,154,180,and 209) were 117.58 ng g À1 lw for Luqiao and 357.44 ng g À1 lw for Wenling (Zhao et al, 2010).…”
Section: Level Of Dechlorane Plus and Its Dechlorinated Analogmentioning
confidence: 99%
“…We found four studies that researched the presence of PBDEs metabolites in blood 22,24,25,37 Two articles about the presence of PBDEs in breast milk 19,38 and in placenta 19 were reviewed. Two publications 28,39 evaluated the impact of the improvement measure on industrial hygienic implemented in an e-waste company, measuring the changes in the levels of exposure and in the PBDEs congeners pattern.…”
Section: Resultsmentioning
confidence: 99%
“…All the studies reviewed 19,[30][31][32][33] , investigating the connection between work exposure to PBDEs and levels of PBDEs in hair, showed that levels of PBDEs in hair in the exposed population were significantly higher than those in control population (level of evidence 3).…”
Section: Paula Lechuga Vázquez Mª Luisa Paredes Rizomentioning
confidence: 99%
See 1 more Smart Citation